Multipoint observations of plasma phenomena made in space by Cluster. (11th March 2015) - Goldstein, M. L.; Escoubet, P.; Hwang, K.-Joo; Wendel, D. E.; Viñas, A.-F.; Fung, S. F.; Perri, S.; Servidio, S.; Pickett, J. S.; Parks, G. K.; Sahraoui, F.; Gurgiolo, C.; et al.
Abstract : Plasmas are ubiquitous in nature, surround our local geospace environment, and permeate the universe. Plasma phenomena in space give rise to energetic particles, the aurora, solar flares and coronal mass ejections, as well as many energetic phenomena in interstellar space. Although plasmas can be studied in laboratory settings, it is often difficult, if not impossible, to replicate the conditions (density, temperature, magnetic and electric fields, etc.) of space. Single-point space missions too numerous to list have described many properties of near-Earth and heliospheric plasmas as measured both in situ and remotely (seehttp://www.nasa.gov/missions/#.U1mcVmeweRY for a list of NASA-related missions). However, a full description of our plasma environment requires three-dimensional spatial measurements. Cluster is the first, and until data begin flowing from the Magnetospheric Multiscale Mission (MMS), the only mission designed to describe the three-dimensional spatial structure of plasma phenomena in geospace. In this paper, we concentrate on some of the many plasma phenomena that have been studied using data from Cluster. To date, there have been more than 2000 refereed papers published using Cluster data but in this paper we will, of necessity, refer to only a small fraction of the published work. We have focused on a few basic plasma phenomena, but, for example, have not dealt with most of the vast body of work describing dynamical phenomena in Earth's magnetosphere, including the dynamics of current sheets in Earth's magnetotail and the morphology of the dayside high latitude cusp. Several review articles and special publications are available that describe aspects of that research in detail and interested readers are referred to them (see for example, Escoubet et al.2005 Multiscale Coupling of Sun-Earth Processes, p. 459, Keith et al.2005 Sur. Geophys. 26, 307–339, Paschmann et al.2005 Outer Magnetospheric Boundaries: Cluster Results, Space Sciences Series of ISSI . Berlin: Springer, Goldstein et al.2006 Adv. Space Res. 38, 21–36, Taylor et al.2010 The Cluster Mission: Space Plasma in Three Dimensions, Springer, pp. 309–330 and Escoubet et al.2013 Ann. Geophys. 31, 1045–1059).